2020
DOI: 10.1051/parasite/2019080
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii in women of childbearing age and during pregnancy: seroprevalence study in Central and Southern Italy from 2013 to 2017

Abstract: Toxoplasmosis is a worldwide health problem. Infection in pregnant women can result in severe fetal morbidity or in subclinical neonatal infection; most subclinical cases develop ocular and neurological sequelae. The purpose of this serological study was to assess the prevalence of Toxoplasma gondii in two populations of women of childbearing age in Siena (Tuscany, Central Italy) and Bari (Apulia, Southern Italy) between 2013 and 2017 and in a group of pregnant women in Bari in 2016–2017. Serum samples were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
3
15
2
Order By: Relevance
“…This study demonstrated the presence of T. gondii IgG antibodies in serum samples of 41.16% of women of childbearing age living in Arad county, a well-known endemic area of Romania. The seroprevalence was higher than that reported by other European investigators: 24.1% in Northern Kosovo and Metohija [ 22 ], 22.3% in Italy [ 5 ], 22% in Portugal [ 7 ], and 29.1% in Croatia [ 25 ]. The differences in seroprevalence of T. gondii IgG antibodies between countries can be explained by different nutritional habits, as well as sociodemographic and cultural factors [ 17 , 19 ].…”
Section: Discussioncontrasting
confidence: 57%
“…This study demonstrated the presence of T. gondii IgG antibodies in serum samples of 41.16% of women of childbearing age living in Arad county, a well-known endemic area of Romania. The seroprevalence was higher than that reported by other European investigators: 24.1% in Northern Kosovo and Metohija [ 22 ], 22.3% in Italy [ 5 ], 22% in Portugal [ 7 ], and 29.1% in Croatia [ 25 ]. The differences in seroprevalence of T. gondii IgG antibodies between countries can be explained by different nutritional habits, as well as sociodemographic and cultural factors [ 17 , 19 ].…”
Section: Discussioncontrasting
confidence: 57%
“…This could be explained by the fact that Morocco, Tunisia, and Algeria share the same culinary habits, cultural habits, and climatic conditions. However, the results of other surveys show a lower and higher prevalence in different areas in Africa, in Europe, and in Asia: 27% in Sudan [ 17 ], 35.6% in Ethiopia [ 18 ], 44% in Tanzania [ 19 ], 47% in Benin [ 20 ], 13.8% in Italy [ 21 ], 31.5% in Austria [ 22 ], 55.8% in Romania [ 23 ], 31% in Turkey [ 24 ], 33% in Iran [ 25 ], 34.5% in Pakistan [ 26 ], 82.6% in Lebanon [ 27 ], and 35.8% in Peru [ 28 ]. This variation in the rate of T. gondii infection between countries and regions could be attributed to dietary habits, health standards, lack of awareness of disease transmission, and the socioeconomic level.…”
Section: Discussionmentioning
confidence: 99%
“…In the same context, a study carried out in Abidjan, Côte d'Ivoire, proved that seroprevalence decreases with increasing age [35]. However, several studies have shown that the infection rate increases with age, due to high exposure to sources of infection [4,8,12,28]. Contrarily, research performed by Fakhfakh and Elsheikha did not find any correlation between the presence of T. gondii antibodies and age [9,11].…”
Section: Discussionmentioning
confidence: 99%